EXPLORING TEACHERS’ STRATEGIES IN TEACHING ENGLISH TO YOUNG LEARNERS: CLASSROOM PRACTICES, RATIONALES, AND CHALLENGES - Nancy Angelia Purba (Sensei International Journal of Education and Linguistic, 2025)
Teaching English to young learners is not the same as teaching adults because children have a short attention span and they learn better through fun activities. Therefore the teacher must have good strategies. This study discusses the strategies of teachers in teaching English to young learners. The study used a qualitative method. The data were collected through observation, interview, and documentation in some elementary schools. The data were analyzed descriptively. The result of the study shows that the teachers use various strategies such as songs, pictures, games, and repetition, and the teachers also have their own reasons for using those strategies. However there are still some obstacles in the field. Therefore it is suggested that the teachers should be given more training so that the teaching of English for young learners can be better.